C-terminal Lysine-Linked Magainin 2 with Increased Activity Against Multidrug-Resistant Bacteria - Lorenzon, Esteban N. [UNESP]; Santos-Filho, Norival A. [UNESP]; Ramos, Matheus A. S. [UNESP]; Bauab, Tais M. [UNESP]; Camargo, Ilana L. B. C.; Cilli, Eduardo M. [UNESP] (Bentham Science Publ Ltd, 2016)
Due to the growing problem of antibiotic-resistant microorganisms, the development of novel antimicrobial agents is a very important challenge. Dimerization of cationic antimicrobial peptides (cAMPs) is a potential strategy for enhancing antimicrobial activity. Here, we studied the effects of magainin 2 (MG2) dimerization on its structure and biological activity. Lysine and glutamic acid were used to synthesize the C-and N-terminal dimers of MG2, respectively, in order to evaluate the impact of linker position used to obtain the dimers. Both MG2 and its dimeric versions showed a random coil structure in aqueous solution. However, in the presence of a structure-inducing solvent or a membrane mimetic, all peptides acquired helical structure. N-terminal dimerization did not affect the biological activity of the peptide. On the other hand, the C-terminal dimer, (MG2)(2)K, showed antimicrobial activity 8-16 times higher than that of MG2, and the time required to kill Escherichia coli was lower. The enhanced antimicrobial activity was related to membrane permeabilization. (MG2)(2)K was also more active against multidrug-resistant bacteria of clinical origin. Overall, the results presented here demonstrate that C-terminal lysine-linked dimerization improve the activity of MG2, and (MG2)(2)K can be considered as a potential antimicrobial agent.
Keywords: Antimicrobial activity; circular dichroism; dimerization; magainin 2; membrane permeabilization; multi-drug resistant bacteria